Contribution of Ergotoxicology to the Determination of Actual PPE Effectiveness in Protecting Users From Phytosanitary Risks. From Contamination Analysis to the Collective Whistle-Blowing Process - Alain Garrigou; Isabelle Baldi; Philippe Dubuc (Perspectives Interdisciplinaires sur le Travail et la Santé)
This paper presents the results of an ergotoxicologic study on the effectiveness, in real-life conditions, of the protective suits recommended by preventionists. The arguments presented in the paper are based on the Pestexpo study conducted by Isabelle Baldi (Baldi et al. (2002) and Baldi et al. (2006)), which involved analyzing the exposure of vineyard workers to plant protection products by using an ergo-toxicologic approach. The point is to identify different types of exposure by taking into account the characteristics of the actual work (as opposed to what the operators are supposed to be doing) as an outcome of personal, technical and organizational determinants. We were able to point at the permeation of the fabric used for some of the suits. Indeed, after further discussion with PPE manufacturers, it would appear that the suits recommended for agricultural activities were initially developed for industrial purposes and that since farming is just a market niche, these suits may not have been tested for plant protection products, not even for the most common ones. We will explore this topic in terms of organizational and technical failure (Reason, 2004) in the personal protective equipment (PPE) design, testing and standardization process. We will also present the collective whistle-blowing process that was initiated.